TRACER STUDY: STRATEGIES FOR STRENGTHENING ACADEMIC PROGRAM IN THE 5.0 ERA - Khatib A.Latief; Eka Januar; Muhammad Rizki; Cut Nur Nabilah Fildzah; Rizqiya Safira (JURNAL TARBIYAH, 2025)
As technology evolves through the 4.0 Industrial Revolution and the 5.0 Era, higher education institutions must adapt to remain relevant. Tracer Studies are crucial for tracking alumni career paths and assessing the effectiveness of academic programs, ensuring that curricula align with industry needs. Without regular updates based on alumni data, graduates may experience skills mismatches, which can negatively impact employability and hinder institutional growth, leading to decreased enrolment, financial difficulties, and challenges in attracting faculty. UIN Ar-Raniry Banda Aceh, with over 55,000 graduates, faces challenges due to the lack of a reliable alumni database. Fragmented data on alumni career paths hinders effective engagement and development. Tracer Studies can address this by providing valuable insights into alumni outcomes and identifying gaps in curricula. This study is also aligned with Indonesia’s Eight Key Performance Indicators, focusing on alumni employability and professional success. For UIN Ar-Raniry, it is critical that alumni qualifications meet the evolving demands of the job market, especially in science-related fields. Additionally, Tracer Studies help institutions meet accreditation requirements from Indonesia's National Accreditation Board for Higher Education, ensuring academic programs remain relevant and effective. To address these issues, from January to June 2024, UIN conducted a tracer study on alumni from 2021, 2022, and 2023 in Aceh Besar, Banda Aceh, and Sabang. Data were collected through online questionnaires, blended interviews, and focus group discussions (FGD). The study found that out of 460 respondents, 102 alumni are employed, with 12 being entrepreneurs. Notably, 76% found jobs within six months, although 33.5% were not actively seeking employment. Alumni users expressed high satisfaction with alumni leadership skills and integrity, despite challenges like limited job openings and networking opportunities. Ultimately, this study is essential for evaluating how well institutions meet labor market demands, refining curricula, and strengthening alumni relations. By conducting regular tracer studies, UIN Ar-Raniry Banda Aceh can ensure its graduates are equipped with the necessary skills, improve alumni engagement, and contribute more effectively to regional and national development.